Repair of peripheral nerve injuries using a prevascularized cell-based tissue-engineered nerve conduit. (January 2022) - Thibodeau, Alexane; Galbraith, Todd; Fauvel, Chantal M.; Khuong, Hélène T.; Berthod, François
Abstract: One of the major challenges in the development of a larger and longer nerve conduit for peripheral nerve repair is the limitation in oxygen and nutrient diffusion within the tissue after transplantation preventing Schwann cell and axonal migration. This restriction is due to the slow neovascularization process of the graft starting from both nerve endings. To overcome this limitation, we propose the design of a living tissue-engineered nerve conduit made of an internal tube with a three-dimensional structure supporting axonal migration, which is inserted inside a hollow external tube that plays the role of an epineurium and is strong enough to be stitched to the severed nerve stumps. The internal tube is made of a rolled living fibroblast sheet and can be seeded with endothelial cells to promote the formation of a network containing capillary-like structures which allow rapid inosculation with the host nerve microvasculature after grafting. Human nerve conduits were grafted in immunodeficient rats to bridge a 15 mm sciatic nerve gap. Human capillaries within the pre-vascularized nerve conduit successfully connected to the host circulation 2 weeks after grafting. Twenty-two weeks after surgery, rats transplanted with the nerve conduits had a similar motor function recovery compared to the autograft group. By promoting rapid vascularization of the internal nerve tube from both ends of the nerve stumps, this endothelialized nerve conduit model displays a favorable environment to enhance axonal migration in both larger caliber and longer nerve grafts.